2004
DOI: 10.3950/jibiinkoka.107.25
|View full text |Cite
|
Sign up to set email alerts
|

Histological Study on the Effects of Ethanol Injection on Month Mucosa Contraction Loss

Abstract: We previously reported that a loss of contraction in the mucosal tissue of the palate arch is effectively induced by ethanol injections of moderate concentration and dosage. The present study was performed to obtain more information on how such ethanol injections induce contraction loss in mucosa tissue. Guinea pigs of both sexes were used in this study. The left arch of the palate mucosa was injected with 2 microliters of 70% ethanol and used as the experimental group. The right arch of the palate mucosa of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…No significant differences in these changes were observed between the E-and E/Dex-injected tissue groups up to day 5 after injection. These results closely resemble histological changes reported for intramucosal injections in guinea pig oral mucosa, which has tissue properties similar to those of human inferior turbinate mucosa [2,3].…”
Section: Target Gene Forward Primer Reverse Primersupporting
confidence: 86%
See 2 more Smart Citations
“…No significant differences in these changes were observed between the E-and E/Dex-injected tissue groups up to day 5 after injection. These results closely resemble histological changes reported for intramucosal injections in guinea pig oral mucosa, which has tissue properties similar to those of human inferior turbinate mucosa [2,3].…”
Section: Target Gene Forward Primer Reverse Primersupporting
confidence: 86%
“…We first studied macroscopic level and histological changes after intradermal injection of 70% E, E/Dex, or Sa to determine whether mouse skin could be used as an intramucosal injection model for the nasal mucosa, which is the intended target of the drug, as described previously [2]. Although vesicular swelling appeared at all the sites immediately after intradermal injection, it abated on day 2.…”
Section: Establishment Of An In Vivo Ethanol Tissue-damage Model By Umentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Ethanol which has been used for many years for liver tumor ablation has also been used experimentally as a submucosal injection for restricted ablation. 11,12,17 It has also been shown that a mixture of ethanol/steroid injected into the elongated uvula and soft palate resulted in shortening of the uvula and improvement in snoring. 13 There is no study that com-…”
Section: Resultsmentioning
confidence: 99%